Organic or inorganic zinc in poultry nutrition: a review. Issue 4 (27th October 2017) - ABD EL-HACK, M.E.; ALAGAWANY, M.; ARIF, M.; CHAUDHRY, M.T.; EMAM, M.; PATRA, A.
Abstract : Zinc (Zn) is an essential component in animal and poultry metabolism of various biochemical pathways. It serves as a nutrient and also as a feed additive for improving reproductive functions, productive indices, cellular immunity, normal growth and the maintenance of feathers, bone tissues as well as appetite. Furthermore, Zn has many roles as an antioxidant agent. This mineral is essential for hormone function, including pancreatic (insulin and glucagon), sex and growth hormones. It is a part of more than 300 enzymes that are involved in the metabolism of protein, energy, carbohydrates and nucleic acids. Previous studies demonstrated many beneficial impacts of supplemental Zn on different physiological and immunological functions above the established concentration in diets, including alleviating heat stress. Zinc supplementation in layer diets increases albumen weight, and may alter egg shell thickness and total egg weight. Zinc deficiency can cause a fraying of the feathers and retardation in growth of broilers. Different Zn sources (organic or inorganic) positively impact health and performance in poultry including meat or egg production, feed intake and conversion efficiency, carcass traits, blood parameters and apparent nutrient digestibility. This review compares and provides a review of the nutritional and physiological aspects of different Zn sources.